Rezension von: Vann, James Allen, The Making of a state - Mclntosh, Terence (Württembergisch Franken, 1985)
James Allen Vann: The Making of a State. Württemberg, 1593-1793. Ithaca, London: Cornell University Press 1984. 321 S.